Nyai Ontosoroh's Capitals Amid the Challenges of Postcolonialism in Bumi Manusia: A Bourdieu's Critical Reading - R Hariyani Susanti (Jurnal Bahtera: Jurnal Pendidikan, Bahasa, Sastra, dan Budaya, 2023)
This literary research delves into the life of Nyai Ontosoroh, who lived during postcolonialism and societal gender stereotypes. It aims to analyze the tactics she used to make the most of her social, cultural, and economic capital. This research will employ a qualitative approach to analyze the life and experiences of Nyai Ontosoroh using Bourdieu's critical reading framework. The study will utilize secondary sources to identify and categorize the different forms of capital available to the character and examine how they intersected with her experiences of postcolonialism and gender stereotypes, which provides a lens to understand how people can leverage different forms of capital to achieve their goals. Through this analysis, the study discovered that Nyai Ontosoroh was able to take advantage of the capitals provided by her illegitimate husband to navigate the difficulties of being a woman in the era. The findings of the research showcase the remarkable abilities of Nyai Ontosoroh in utilizing her capitals and highlight the critical role of social capital in shaping the experiences of women during this historical time. This study highlights the significance of understanding the intricate relationships between gender, postcolonialism, and social capital, providing valuable insights for scholars and readers alike.